Exploring spiritual intelligence in academe - Hernandez, Antoinette Bass (2005)
This research is an attempt to find out whether top officials in the academe, specifically higher education institutions, exhibit spiritual intelligence. The participants were 59 higher education institutions (HEI) presidents who served as presidents for at least two years and 8 experts. The research design made use of the conventional disciplined integral inquiry method recently labeled by Creswell (2005) as the concurrent transformative strategy. The spiritual intelligence was measured with the PsychoMatrix Spirituality Inventory (PSI)of Wolman (2001) while the management styles were measured through an adapted instrument of Blake and Mouton (1985). The results yielded 16 notions of spiritual intelligence. Results culminated in alternative instruments, a theory of Filipino Management Style anchored in spiritual intelligence and possible areas of theory, practice and research that may further strengthen spiritual component in management.